An atypical case of retinal pigment epithelium tear with remodeling and visual preservation - Charles Jit Teng Ong; Chui Ming Gemmy Cheung (Taiwan Journal of Ophthalmology)
This report describes a patient with polypoidal choroidal vasculopathy (PCV) with fovea-involving retinal pigment epithelium (RPE) tear that showed tissue remodeling with a good visual outcome. Imaging over the patient’s clinical course from 2019 was reviewed. A 74-year-old female presented with left submacular hemorrhage and a large multi-lobular pigment epithelial detachment. Left eye vision was 6/19 at the presentation. Indocyanine green angiography (ICGA) revealed underlying PCV. One month after initiation of intravitreal aflibercept (IVA, Bayer), she developed fresh subretinal hemorrhage. An RPE tear of 1 disc area in size, centered over the fovea was diagnosed. The torn RPE edge was scrolled up temporal to the fovea on spectral-domain optical coherence tomography (SD-OCT), with hypertransmission into the choroid observed over the area of RPE loss. Left eye vision after the RPE tear was 6/15. Over the next 2 months, the subretinal hemorrhage resolved following further IVA. At month 3, fundus autofluorescence (FAF) demonstrated hypo-autofluorescence while fundus fluorescein angiography (FFA) and ICGA showed a window defect corresponding to the area of RPE tear. On SD-OCT, there was a faint hyper-reflective layer where one might expect the RPE layer to be. Serial SD-OCT scans over 5 years revealed increasing prominence of the hyperreflective layer between the ellipsoid zone and Bruch’s membrane. FAF remained hypo-autofluorescent. At the last review, the patient retained 6/9 vision. We report a case of fovea-involving RPE tear documented with multimodal imaging with good visual outcome, which is atypical. Serial OCT suggests tissue remodeling may explain the functional preservation.